2018
DOI: 10.17816/ecogen16153-59
|View full text |Cite
|
Sign up to set email alerts
|

A molecular genetic research of the Triticum sinskajae A. Filat. et Kurk. by RAPD analysis and by comparing the nucleotide sequences of the variable intergenic region of the petN-trnC-GCA chloroplast genome and intron of the histone H3.2 gene

Abstract: Background. Triticum sinskajae A. Filat. et Kurk. was discovered in the early 70th in the last century at the regular reproduction in the Central Asian and Dagestan VIR-stations of T. monococcum samples. Materials and methods. The objects of the study were 4 species of diploid wheat — Triticum urartu Thum. ex Gandil. (lines k-62477, k-62465), Triticum monococcum L. (lines k-20970, k-39471), Triticum boeoticum Boiss. (lines k-59161, k-28132, k-40118) and Triticum sinskajae A. Filat. et Kurk. (line k-48993… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…sinskajae is a little-studied diploid wheat, which was previously thought to be formed as a result of a spontaneous mutation of T. monococcum (Filatenko and Kurkiev 2000). Previously, using classical molecular genetic analysis (Kuluev et al 2018), as well as by comparing the nucleotide sequences of plastid genomes (Kuluev et al 2020), we obtained data indicating the existence of a separate species of diploid wheat -T. sinskajae. On the other hand, Sinskaya wheat exhibits complete genetic compatibility with T. monococcum and T. boeoticum (Kurkiev and Filatenko 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sinskajae is a little-studied diploid wheat, which was previously thought to be formed as a result of a spontaneous mutation of T. monococcum (Filatenko and Kurkiev 2000). Previously, using classical molecular genetic analysis (Kuluev et al 2018), as well as by comparing the nucleotide sequences of plastid genomes (Kuluev et al 2020), we obtained data indicating the existence of a separate species of diploid wheat -T. sinskajae. On the other hand, Sinskaya wheat exhibits complete genetic compatibility with T. monococcum and T. boeoticum (Kurkiev and Filatenko 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These two wheats evolved for a long time in reproductive isolation, but possibly within the same range. Of course, T. sinskajae separated from the general line of diploid wheats or from T. monococcum later than other einkorns, but nevertheless managed to accumulate quite a signi cant number of mutations both in the nuclear (Goncharov et al 2007, Watanabe 2017, Kuluev et al 2018) and in the chloroplast genomes. When deciding on the species identity of T. sinskajae, it may be useful to analyze the similarity of plastid genomes in representatives of the genus Aegilops, in which, despite very close morphological similarity, many species have been identi ed.…”
Section: Discussionmentioning
confidence: 99%
“…Such primers enable to amplification of DNA segments that are located quite close to each other in the inter-microsatellite region. ISSR-PCR markers have a dominant inheritance pattern (Selezneva and Akhmedov, 2016;Bardukov et al, 2014;Kuluev et al, 2018).…”
Section: Population-genetic Analysis Of Speciesmentioning
confidence: 99%
“…is the youngest taxon discovered in the accession K-20970 of cultivated einkorn wheat in the second half of 20th century (Filatenko, Kurkiev, 1975). In Russia, T. sinskajae is represented by a single accession K-48993, in many studies (Goncharov et al, 2007;Kuluev et al, 2018). The authors stated that this species was a natural naked mutant of hulled diploid T. monococcum.…”
Section: Introductionmentioning
confidence: 99%
“…To develop early, freethreshing and semi-dwarf einkorn lines, Watanabe (2017) utilised two different genes determining free threshing of einkorn wheat, one sog (soft glume) of T. sinskajae and another sos (soft spike) of T. monococcum. Kuluev et al (2018) found differences between T. sinskajae and T. monococcum in the variable region of the histone gene H3.2, and the random amplified polymorphic DNA (RAPD) analysis showed the presence of unique polymorphic loci in T. sinskajae.…”
Section: Introductionmentioning
confidence: 99%